Kualitas Pelayanan Pajak Berdasarkan Persepsi Wajib Pajak - Lusy Suprajadi; Sylvia Fettry E. M; Granita Chrysantiami (Bina Nusantara University, 2008)
Nation independence is characterized by its ability to finance development from taxation. Every citizen fulfilling objective requirements has an obligation to pay tax and therefore categorized as Wajib Pajak (Tax Payer). But in real practices, many people hide their income in order to avoid tax payment, moreover the decline of tax revenue influences the nation’s ability to finance its sustainable development and managing the country. This condition causes Direktorat Jenderal Pajak (DJP) to enhance itself by modernizing administration and tax services. The implementation of this modernization concept in Bandung includes the development of Kantor Pelayanan Pajak (KPP) Madya Bandung. This research is done to know whether the modernization of taxation increases the service quality in KPP Madya compared to the previous service quality in the KPP. The data in this research are collected by closed questionnaire distributed to Wajib Pajak registered in KPP Madya Bandung as respondents. Sample is designated based on Simple Random Sampling technique. Hyphotheses are tested by parametric statistic paired samples t-test with an error level of 5%. The result of this research is that the service quality based on Wajib Pajak’s perception after the modernization in KPP Madya Bandung is better than before the modernization in the KPP previously.